DEVELOPMENT OF TURKESTAN FROM THE GREAT SILK ROAD - Baltabayeva А. Yu.; Yesbalayeva R. Zh.; Shaikhystamova M. B.; Naciye Yildiz; Beskempirova A. U. (Scientific Journal of Pedagogy and Economics, 2019)
This article analyzes the value of the of Arystanbab and Hodja Akhmet Yassawi knowledge, the world-renowned works of today, including the development of civilizations such as Turkestan, Otyrar along the Great Silk Road. They are narrated from the standpoint of historical truth and artistic judgment, from the archaic legends and stories to the story of Yassawi. At civilizations current, he proposed to pay special attention to the Great Silk Road in the article of the First President of the Nation N.A. Nazarbayev “Seven facets of Great Steppe”. Also, by the Decree of him, the establishment of Turkestan as the regional center and the resumption of the old city on the basis of medieval architectural design today can be seen as a wonder of Turkic civilization. Turkestan is also a religious center that hosts all Muslims. In the article Akhmet Yassawi’s “Divan-i-Hikmet” is literary, historical, philosophical and educational.